Galaxy Clustering in Large Redshift Surveys - Hawkins, Ed (2003)
This thesis analyses the large scale distribution of galaxies in two recently completed redshift surveys and develops models to infer estimates of redshift-space distortions. These models demonstrate that coherent infall cannot be neglected in analyses of peculiar velocities as previous works have claimed.